Inside Back Cover: Detergent‐Assisted Braking of Peptide Translocation through a Single‐Layer Molybdenum Disulfide Nanopore (Small Methods 11/2020). Issue 11 (12th November 2020) - Si, Wei; Sun, Qianyi; Chen, Chang; Yu, Meng; Sha, Jingjie; Zhang, Yin; Kan, Yajing; Chen, Yunfei
Abstract : In article number 1900822 by Wei Si, Jingjie Sha, Yunfei Chen, and co‐workers, the capability of peptide sequencing by using a solid‐state nanopore is systematically investigated. Due to the strong interaction between the hydrophobic parts of the peptide and nonionic detergents, the detergents can control the protein translocation process through the nanopore but do not affect the discrimination of single amino acids.